El arte como didáctica de enseñanza-aprendizaje de las matemáticas (2020)
Art as a didactic of teaching-learning mathematics The interest of this research was founded in using art as a tool for teaching mathematics. Therefore, I seek to use art as a teaching strategy to stimulate and improve the motivation and academic performance of students in the subject of mathematics. This is because, in the synthetic quality index, the subject of mathematics yields low academic results among which the failure of the subject is an alarming factor. In contrast to previous studies which focused on the teaching of separate subjects, I intend to show that, by linking art in mathematics teaching in an interdisciplinary curriculum, the overall general development of students can be achieved (cognitive, emotional, social and physical), in addition to providing a variety of experiences which improve and facilitate the teaching exercise, that in turn, creates a learning environment in which students can discover their strengths, abilities, intelligences, and value them and communicate them in an assertive way. In Robinson?s words, Many brilliant people do not believe in their abilities because what they stood out in school was not valued or even stigmatized. The consequences are catastrophic for individuals and for the health of our communities (Robinson, 2015, p. 6). In implementing this strategy, we seek to prevent our students from becoming part of that group of people referred to by Ken Robinson, since the results obtained in recent years in mathematics are very low and the group of students is perceived as with an air of failure and at the same time, as an avoidance of the problem. This intervention was performed on a course of 39 eighth grade students during the third quarter of 2018 and the first quarter of 2019 and part of the second. The method used was action research, as we seek to improve teaching practices and establish collaborative paths between art and mathematics in order to improve the academic performance of students affected.